Composite sealing material for medium-temperature solid oxide fuel cell as well as preparation method and application of composite sealing material

By combining tetragonal t-ZrO2 ceramic particles with borosilicate glass powder and utilizing the stress-induced phase transformation toughening mechanism, a composite sealing material was prepared, which solved the problems of high brittleness of sealing glass and low joint strength, and achieved a highly efficient sealing effect.

CN119263645APending Publication Date: 2025-01-07CHONGQING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411581309.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing solid oxide fuel cell sealing glass materials are brittle and have low joint strength, making it difficult to meet the dynamic load requirements of mobile SOFCs.

Method used

A composite sealing material was prepared by combining tetragonal t-ZrO2 ceramic particles with borosilicate glass powder, dispersing the powder in an agate mortar and homogenizing it with ultrasonic vibration, and combining the stress-induced phase transformation toughening mechanism.

Benefits of technology

It significantly improves the fracture toughness and crack resistance of sealing materials, increases the shear strength of joints by 8.5 times, reduces the brittleness factor, and achieves high sealing strength and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263645A_ABST
    Figure CN119263645A_ABST
Patent Text Reader

Abstract

The invention discloses a composite sealing material for a medium-temperature solid oxide fuel cell as well as a preparation method and application of the composite sealing material, and belongs to the technical field of solid oxide fuel cell materials. The defects that strengthening phase particles are not uniformly distributed in a glass matrix and are easy to agglomerate are successfully overcome by matching mortar mixing with ultrasonic concussion; the preparation method effectively prevents the t-ZrO2 nano strengthening phase in the composite glass from phase change in the preparation process, keeps the original tetragonal crystal structure of t-ZrO2 in the glass, and is beneficial to exerting the phase change toughening characteristic of the t-ZrO2 strengthening phase. Based on the preparation process, the phase change toughening characteristic of the t-ZrO2 ceramic particles is fully utilized, the problems that the sealing glass is high in brittleness and easy to crack are effectively solved, and the composite sealing glass material with high fracture toughness and low brittleness is obtained. In addition, by optimizing the composite sealing material, the connection quality of the joint is remarkably improved, and the load resistance and long-term stability of the solid oxide fuel cell stack are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid oxide fuel cell materials, and in particular to a composite sealing material for medium-temperature solid oxide fuel cells, and a preparation method and application thereof. Background Art

[0002] Research on solid oxide fuel cells / electrolyzers (SOFC / SOEC) has attracted much attention in recent years. This technology plays an important role in the field of energy conversion. The uniqueness of SOFC / SOEC technology is that it can directly convert the chemical energy of a variety of fuels into electrical energy, including hydrogen, methanol, ethanol, natural gas and hydrocarbons, so it has a wide range of application prospects.

[0003] The high-efficiency energy conversion characteristics of this technology make it occupy an important position in fuel cell technology. Its power generation efficiency can reach 40-60%, and the conversion efficiency achieved by the heat-electricity co-generation method can even be as high as 80% or more. Compared with the traditional Carnot cycle, SOFC / SOEC technology is not limited by it, so it has greater flexibility and applicability. More importantly, SOFC / SOEC technology is closely interconnected with renewable energy, and can use fuels such as hydrogen generated by renewable energy for electrical energy conversion, thereby promoting efficient energy utilization and sustainable development. Therefore, this technology is expected to become one of the important technologies for solving global energy problems and promoting the development of clean energy, providing a feasible technical idea for achieving sustainable development goals.

[0004] Nevertheless, many technical bottlenecks remain to be solved before SOFC / SOEC technology can be widely used. Among them, the technical difficulties in sealing are particularly prominent, so the development of efficient sealing technology has also become a research hotspot and focus in the field of SOFC / SOEC. Taking the flat SOFC cell stack as an example, the sealing joints of the cell stack have long faced harsh service conditions, including the dual challenges of strong chemical corrosion and thermal stress. This requires the sealing material to have excellent high-temperature stability and corrosion resistance. Among them, glass sealing materials have attracted much attention due to their self-healing ability at high temperatures and adjustable performance, and are considered to be one of the best choices for achieving reliable connection of SOFC cell stacks. In the past decade, researchers have indeed made a series of progress and developed many glass and glass-ceramic sealing materials with strong thermal stability. However, the problem of high brittleness of SOFC sealing glass still exists. Therefore, it is necessary to focus on solving the above problems, find glass sealing materials that are more resistant to high temperatures, thermal stress and excellent in mechanical properties, and take effective process measures to improve the stability and reliability of sealing joints, so as to achieve long-term stable operation of SOFC / SOEC systems.

[0005] In order to solve the above problems, researchers adopted the strategy of introducing a reinforcing phase to effectively improve the thermal stability and mechanical properties of the sealing material. CN114436533A discloses a composite sealing material for solid oxide fuel cells, a preparation method and an application thereof, and improves the mechanical properties of the composite sealing material by adding a silica alkali calcium stone powder reinforcing phase to the sealing glass powder. CN112928299B discloses a high-temperature composite sealing material and its application, the composite sealing material comprises an expansion sealing component (component A) and a molten sealing component (component B), wherein component A is a single metal, an alloy, or a combination of one or more of metal oxides. In the high-temperature sealing stage, component A reacts chemically with the molten sealing component and produces a volume expansion effect, achieving the effect of pressureless sintering sealing, which is particularly suitable for tubular SOFC sealing of narrow gaps or gaps. In addition, other patents such as US2008 / 0142148, CN10168403A, and CN101148322B improve the viscosity and thermal expansion coefficient of the sealing glass by promoting crystallization through heat treatment or adding a ceramic particle reinforcing phase. Although the existing patents have made some progress in sealing effects, they have not fundamentally solved the problems of high brittleness of sealing glass and low sealing strength of the stack. For example, studies have shown (Investigating the performance of Glass / Al2O3 composite seals in planar solid oxide fuel cells) that the shear strength of the joint obtained by adding alumina ceramic particles as a reinforcement phase is only 3.83MPa, which is far from meeting the dynamic load requirements of mobile SOFC.

[0006] In summary, it is once again shown that the problems of high brittleness of sealing glass and low joint connection strength in the field of glass-sealed SOFC have not been properly solved. Therefore, the present invention proposes a new method, namely the technology of stress-induced phase change toughening of sealing glass, which aims to improve the mechanical properties of sealing glass and the sealing strength of joints, and provides a feasible technical approach for high-quality SOFC glass sealing. Through this method, the current problems of high brittleness of sealing glass and easy cracking induced by thermal stress can be solved, thereby providing a more reliable sealing solution for applications such as mobile SOFC. Summary of the invention

[0007] The purpose of the present invention is to provide a composite sealing material for medium-temperature solid oxide fuel cells, a preparation method and an application thereof. On the one hand, a new preparation process of composite glass sealing materials is developed; on the other hand, the problem of high brittleness and low sealing strength of glass sealing materials is solved by using the phase change toughening mechanism, thereby providing a composite sealing material for medium-temperature solid oxide fuel cells and a sealing method thereof.

[0008] To achieve the above object, the present invention provides a method for preparing a composite sealing material for a medium-temperature solid oxide fuel cell, the steps of which are as follows: Borosilicate glass powder and tetragonal t-ZrO2 ceramic particles are weighed according to mass percentage, dispersed in an agate mortar to obtain a mixed powder, and then the mixed powder and pineneol are successively added into a glass test tube, homogenized again by ultrasonic vibration, and finally a composite sealing material is obtained.

[0009] Preferably, the mass percentage of the borosilicate glass and the tetragonal t-ZrO2 ceramic particles is 60-100:0-40.

[0010] Preferably, the borosilicate glass is 44SiO2-10B2O3-4Al2O3-25SrO-11CaO-6Na2O; the average particle size D of the tetragonal t-ZrO2 ceramic particles is 50 50~500nm.

[0011] Preferably, the weight ratio of terpineol to mixed powder is (2-20):1.

[0012] Preferably, the dispersion time in the agate mortar is 5 to 30 minutes; the ultrasonic oscillation frequency is 20 to 150 KHZ, and the ultrasonic oscillation time is 5 to 30 minutes.

[0013] The present invention also provides a composite sealing material for medium-temperature solid oxide fuel cells prepared by the above preparation method.

[0014] The present invention also provides the sealing application of the composite sealing material prepared above in a medium-temperature solid oxide fuel cell.

[0015] Preferably, the steps of sealing the composite sealing material for a medium-temperature solid oxide fuel cell include: (1) The surfaces of the parent materials to be welded of the electrolyte ceramic and the connector stainless steel are ground flat, and then the electrolyte ceramic is polished and ultrasonically cleaned, and the connector stainless steel is pre-oxidized at 900°C for 120 minutes, and then the composite sealing material is coated on the surface of the parent material to be welded by screen printing and dried; (2) Assemble the base material to be welded coated with the composite sealing material in the form of a sandwich, apply a pressure of 10~100KPa, and send it into a muffle furnace; (3) In an air atmosphere, heat to 300-500°C at a heating rate of 2-10°C / min, keep warm for 10-60 min, then heat to 800-950°C at a heating rate of 2-10°C / min, keep warm for 20-60 min, so as to achieve effective connection between the base material to be welded and the composite sealing material, then cool to 400°C at a cooling rate of 2°C / min, and finally cool the seal with the furnace.

[0016] Preferably, the electrolyte ceramic is one of YSZ ceramic, ScSZ ceramic or GDC ceramic; the connector stainless steel is one of Crofer22H, Crofer22APU, 430 stainless steel or 441 stainless steel.

[0017] Preferably, the thickness of the composite sealing material coated on the surface of the base material to be welded is 50-300 μm.

[0018] Therefore, the present invention provides a composite sealing material for medium-temperature solid oxide fuel cells, a preparation method and an application thereof, which effectively solves two problems in the preparation process of existing composite glass through the two-step method of preliminary mixing in an agate mortar and ultrasonic vibration homogenization. They are: 1. Successfully solve the defect problem of uneven distribution and easy agglomeration of strengthening phase particles in the glass matrix; 2. Effectively avoid the phase change of t-ZrO2 nano-strengthening phase in the composite glass during the preparation process, and maintain the original tetragonal phase crystal structure of t-ZrO2.

[0019] The prepared composite material is used in the sealing of medium-temperature solid oxide fuel cells. After sealing, the phase change toughening strategy of t-ZrO2 is used to effectively solve the problem of high brittleness and easy cracking of the sealing glass, and a composite glass sealing material with high fracture toughness and low brittleness is obtained, ultimately achieving excellent sealing strength.

[0020] Under the induction of external forces such as crack tip stress, the t-ZrO2 grains in the sealing glass of the composite glass sealing material prepared by the present invention undergo a phase change, from tetragonal t-ZrO2 to monoclinic m-ZrO2. On the one hand, the phase change causes the t-ZrO2 grains to expand in volume by 4-7%, generating a compressive stress field at the crack tip, effectively reducing the stress value at the crack tip; on the other hand, the phase change and volume expansion can absorb or consume the energy of crack tip expansion, preventing the crack from continuing to expand. Therefore, the present invention significantly reduces the brittleness of glass, effectively improves its crack resistance, and provides a feasible idea for the application of mobile SOFC stacks. This research result is of great significance in practical applications and is expected to provide a solid technical foundation for the further development and application of SOFC technology.

[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The microscopic morphology of the YSZ / Crofer22H joint obtained by adding 20wt.% t-ZrO2 and adopting the process conditions of "mortar mixing + ultrasonic vibration" in Example 1 of the present invention, wherein (a) is the overall microscopic morphology of the joint; (b) is a partial enlarged view of the glass brazing seam; Figure 2 The distribution morphology and TEM microstructure of 3YSZ nano-ceramic particles in the composite sealing material in Example 1 of the present invention, wherein (a) is the microstructure of 3YSZ nano-ceramic particles; (b) is the SAED result of 3YSZ nano-ceramic particles in Figure (a); (c) is the FFT and IFFT diagram of the glass matrix; (d) is the t-ZrO2 / glass interface; (e) is the FFT and IFFT results of t-ZrO2 nano-ceramic particles; Figure 3 The indentation microscopic morphology of the glass sealing material under the condition of adding 20wt.% t-ZrO2 in Example 1 of the present invention, wherein (a) is the overall morphology of the indentation; (b) is a local enlarged view of the indentation; Figure 4 This is a microscopic morphology of a 430 stainless steel / 430 stainless steel joint with 20 wt.% t-ZrO2 added in Example 2 of the present invention; Figure 5 The microscopic morphology of the YSZ / Crofer22H joint without adding t-ZrO2 in Comparative Example 1 of the present invention, wherein (a) is the overall microscopic morphology of the joint; (b) is a local enlarged view of the YSZ / glass interface; (c) is a local enlarged view of the glass / Crofer22H interface; Figure 6 This is a microscopic morphology of the Crofer22H / Crofer22H joint obtained by adding 20wt.% t-ZrO2 and mixing in a mortar in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, simplifications made without violating the spirit and principle of the present invention should all be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application, and all belong to the scope of protection of the present invention.

[0024] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.

[0025] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.

[0026] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.

[0027] Example 1 This embodiment provides a method for preparing a sealing material for a medium-temperature solid oxide fuel cell and its application.

[0028] The preparation method is as follows: 44SiO2-10B2O3-4Al2O3-25SrO-11CaO-6Na2O borosilicate glass powder and average particle size D are taken in a mass percentage of 80:20. 50 Tetragonal t-ZrO2 ceramic particles with a size of 400 nm were dispersed in an agate mortar for 20 minutes to obtain a mixed powder. The mixed powder and pineneol were added into a glass test tube in a weight ratio of 1:15, and then ultrasonically vibrated at 120KHZ for 10 minutes to obtain a composite sealing material.

[0029] The sealing method of the composite sealing material for medium-temperature solid oxide fuel cells in medium-temperature solid oxide fuel cells is achieved by the following steps: (1) The surfaces of the YSZ ceramic and Crofer22H stainless steel base materials to be welded were ground flat, and then the YSZ ceramic was polished and ultrasonically cleaned. The Crofer22H stainless steel was pre-oxidized at 900°C for 120 minutes. Then, a composite sealing material with a thickness of 100 μm was coated on the surface of the base material to be welded by screen printing and dried. (2) Assemble the base material to be welded coated with the composite sealing material in the form of a sandwich, apply a pressure of 50 KPa, and place it into a muffle furnace; (3) In an air atmosphere, heat to 300°C at a heating rate of 5°C / min and keep warm for 30 minutes. Then heat to 850°C at a heating rate of 5°C / min and keep warm for 30 minutes to achieve effective connection between the base material and the composite sealing material. Then cool to 400°C at a cooling rate of 2°C / min. Finally, the seal is cooled in the furnace.

[0030] like Figure 1 As shown in the figure, there are no obvious cracks in the microscopic morphology of the YSZ / Crofer22H joint obtained in this embodiment, the agglomeration defects and hole defects of the white t-ZrO2 particles are significantly reduced, the porosity is only 0.14%, and the t-ZrO2 particles are evenly distributed in the glass brazing joint. Through the transmission electron microscopy analysis of the t-ZrO2 particles in the glass, it is found that the t-ZrO2 particles after the sealing process still maintain the original tetragonal phase crystal structure and are well combined with the glass matrix. The specific microstructure results are shown in Figure 2 In addition, the mechanical properties of the glass solder joint obtained in this example were tested, and the fracture toughness of the glass solder joint was found to be 2.69 MPa·m 1 / 2 , the elastic modulus is 95.16 GPa. Compared with the fracture toughness of the borosilicate glass prepared in Comparative Example 1, the fracture toughness value of the composite sealing material prepared in this embodiment is increased by 1.5 times, and the brittleness factor is reduced to 1.64 μm. 1 / 2 .like Figure 3 As shown, after the glass was subjected to microhardness indentation testing, it was found that the composite glass brazing joint had good crack resistance. When the radial crack encountered t-ZrO2 particles, multiple crack deflection and crack bridging mechanisms occurred, and finally crack closure was formed. Through analysis, it can be seen that the essence of this toughening is that t-ZrO2 undergoes a phase change toughening mechanism under stress-induced conditions. The tetragonal phase t-ZrO2 transforms to the monoclinic phase m-ZrO2, accompanied by 3~7% volume expansion and shear deformation. In addition, the obtained joint shear strength is 28.1±4.3MPa. Compared with Comparative Example 1, the joint shear strength obtained in this embodiment is increased by 8.5 times, and the standard deviation of the joint shear strength is also reduced to 4.3MPa, which significantly improves the stability of the joint mechanical properties.

[0031] Example 2 This embodiment provides a method for preparing a sealing material for a medium-temperature solid oxide fuel cell and its application.

[0032] The preparation method is as follows: 44SiO2-10B2O3-4Al2O3-25SrO-11CaO-6Na2O borosilicate glass powder and average particle size D are taken in a mass percentage of 80:20. 50Tetragonal t-ZrO2 ceramic particles with a diameter of 400 nm were dispersed in an agate mortar for 20 minutes to obtain a mixed powder. The mixed powder and pineneol were added into a glass test tube in a weight ratio of 1:20, and then ultrasonically vibrated at 100KHZ for 10 minutes to obtain a composite sealing material.

[0033] The sealing method of the composite sealing material for medium-temperature solid oxide fuel cells in medium-temperature solid oxide fuel cells is achieved by the following steps: (1) Grind the surface of the 430 stainless steel base material to be welded flat, and then ultrasonically clean it. After completing the above pretreatment process, pre-oxidize the 430 stainless steel at 900°C for 120 minutes. Then, screen print the composite sealing material with a thickness of 100μm on the surface of the pre-oxidized 430 base material and dry it; (2) Assemble the 430 stainless steel to be welded coated with the composite sealing material in the form of a sandwich structure, apply a pressure of 50 KPa, and place it into a muffle furnace; (3) In an air atmosphere, heat to 300°C at a rate of 5°C / min and keep warm for 30 minutes. Then heat to 825°C at a rate of 5°C / min and keep warm for 30 minutes to achieve effective connection between the base material and the composite sealing material. Then cool to 400°C at a rate of 2°C / min. Finally, the seal is cooled in the furnace. The 430 stainless steel / 430 stainless steel joint obtained in this embodiment has no obvious cracks in its microscopic morphology, and has few pore defects. Figure 4 The shear strength of the joint is 17.4±3.3MPa, which fully demonstrates the high applicability of the phase change toughening mechanism and can also be used in other material sealing fields of solid oxide fuel cells.

[0034] Comparative Example 1 This comparative example provides a preparation method and application of a sealing material for a medium-temperature solid oxide fuel cell.

[0035] The preparation method is as follows: take 44SiO2-10B2O3-4Al2O3-25SrO-11CaO-6Na2O borosilicate glass powder, grind and disperse it in an agate mortar, then add it and pinene alcohol in a weight ratio of 1:2 into a glass test tube, and evenly mix them through ultrasonic vibration to obtain a sealing material.

[0036] The sealing method of the sealing material for medium-temperature solid oxide fuel cells in medium-temperature solid oxide fuel cells is implemented according to the following steps: (1) Grind the surface of the base material to be welded of YSZ ceramic and Crofer22H stainless steel flat, then polish and ultrasonically clean the YSZ ceramic, and pre-oxidize the Crofer22H stainless steel. The pre-oxidation process is 900℃, and the temperature is kept for 120min. Then, a composite sealing material with a thickness of 100μm is coated on the surface of the base material to be welded by screen printing and dried; (2) Assemble the base material to be welded coated with the composite sealing material in the form of a sandwich structure, apply a pressure of 50 KPa, and place it into a muffle furnace; (3) In an air atmosphere, heat to 300°C at a heating rate of 5°C / min and keep warm for 30 minutes. Then heat to 850°C at a heating rate of 5°C / min and keep warm for 30 minutes to achieve effective connection between the base material and the composite sealing material. Then cool to 400°C at a cooling rate of 2°C / min. Finally, the seal is cooled in the furnace.

[0037] like Figure 5 As shown in the figure, without adding t-ZrO2 strengthening phase, the YSZ / Crofer22H joint obtained in this comparative example has no obvious cracks and can also achieve a good interface connection effect. The block and needle-shaped crystalline phases produced in the joint were characterized by EDS energy spectrum analysis, which were NaAlSiO4 and SrAl2Si2O8 respectively. The fracture toughness of the original borosilicate glass brazing joint is 1.75MPa·m 1 / 2 , the elastic modulus is 85.4 GPa. The joint shear strength obtained in this comparative example is only 3.3±1.1 MPa, which is equivalent to the joint shear strength in the relevant literature that has been published, but it is difficult to meet the sealing strength requirements of the SOFC stack.

[0038] Comparative Example 2 This comparative example provides a preparation method and application of a sealing material for a medium-temperature solid oxide fuel cell.

[0039] The preparation method is as follows: 44SiO2-10B2O3-4Al2O3-25SrO-11CaO-6Na2O borosilicate glass powder and average particle size D are taken in a mass percentage of 80:20. 50 Tetragonal t-ZrO2 ceramic particles with a size of 400 nm were dispersed in an agate mortar for 20 minutes to obtain a mixed powder, and then the mixed powder and pinene alcohol were added into a glass test tube in a weight ratio of 1:2 to obtain a composite sealing material.

[0040] The sealing method of the composite sealing material for medium-temperature solid oxide fuel cells in medium-temperature solid oxide fuel cells is achieved by the following steps: (1) The surface of Crofer22H stainless steel base material to be welded was polished and ultrasonically cleaned, and the Crofer22H stainless steel was pre-oxidized at 900°C for 120 minutes. Then, a composite sealing material with a thickness of 100 μm was coated on the surface of the base material to be welded by screen printing and dried. (2) Assemble the base material to be welded coated with the composite sealing material in the form of a sandwich structure, apply a pressure of 50 KPa, and place it into a muffle furnace; (3) In an air atmosphere, heat to 300°C at a heating rate of 5°C / min and keep warm for 30 minutes. Then heat to 850°C at a heating rate of 5°C / min and keep warm for 30 minutes to achieve effective connection between the base material and the composite sealing material. Then cool to 400°C at a cooling rate of 2°C / min. Finally, the seal is cooled in the furnace.

[0041] like Figure 6 The microstructure of the Crofer22H stainless steel joint shown in the figure shows that a good Crofer22H stainless steel glass brazing connection can be achieved through this comparative example, and there are no obvious cracks on the interfaces on both sides. Nevertheless, the white t-ZrO2 particles inside the brazing joint have obvious agglomeration defects and multiple large-sized hole defects. The generation of the above two defects is mainly caused by the uneven mixing of the composite sealing material during the preparation process, which may further deteriorate the sealing strength and sealing effect of the joint. Compared with comparative example 1, the fracture toughness of the glass brazing joint prepared in this comparative example is 2.54MPa·m 1 / 2 , the elastic modulus is 93.7GPa. The shear strength of the joint is 18.5±7.2MPa, and the shear strength of the joint is increased by 4.6 times, which fully demonstrates the effectiveness of the phase transformation toughening mechanism of t-ZrO2 in improving the mechanical properties of the joint. However, the strength standard deviation of the joint increased to 7.2MPa, showing obvious strength instability, mainly due to the negative effects of t-ZrO2 nanoparticle agglomeration defects and pore defects on the mechanical properties of the joint. Therefore, this also highlights the necessity and importance of developing new composite glass sealing materials.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a composite sealing material for a medium-temperature solid oxide fuel cell, characterized in that: Here are the steps: Borosilicate glass powder and tetragonal t-ZrO2 ceramic particles are weighed according to mass percentage, dispersed in an agate mortar to obtain a mixed powder, and then the mixed powder and pineneol are successively added into a glass test tube, homogenized again by ultrasonic vibration, and finally a composite sealing material is obtained.

2. The method for preparing a composite sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: The mass percentage of the borosilicate glass and the tetragonal t-ZrO2 ceramic particles is 60-100:0-40.

3. The method for preparing a composite sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: The borosilicate glass is 44SiO2-10B2O3-4Al2O3-25SrO-11CaO-6Na2O; the average particle size of the tetragonal t-ZrO2 ceramic particles is D 50 50~500nm.

4. The method for preparing a composite sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: The weight ratio of the pineol to the mixed powder is (2-20):

1.

5. The method for preparing a composite sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: The dispersion time in the agate mortar is 5 to 30 minutes; the ultrasonic oscillation frequency is 20 to 150 KHZ, and the ultrasonic oscillation time is 5 to 30 minutes.

6. A composite sealing material for medium-temperature solid oxide fuel cells, characterized in that: The composite sealing material is prepared by the preparation method described in any one of claims 1 to 5.

7. A composite sealing material for medium-temperature solid oxide fuel cells according to claim 6, characterized in that: The composite sealing material is used for sealing of medium-temperature solid oxide fuel cells.

8. The composite sealing material for medium-temperature solid oxide fuel cells according to claim 7, characterized in that: The steps of sealing the composite sealing material for a medium-temperature solid oxide fuel cell include: (1) The surfaces of the parent materials to be welded of the electrolyte ceramic and the connector stainless steel are ground flat, and then the electrolyte ceramic is polished and ultrasonically cleaned, and the connector stainless steel is pre-oxidized at 900°C for 120 minutes, and then the composite sealing material is coated on the surface of the parent material to be welded by screen printing and dried; (2) Assemble the base material to be welded coated with the composite sealing material in the form of a sandwich, apply a pressure of 10~100KPa, and send it into a muffle furnace; (3) In an air atmosphere, heat to 300-500°C at a heating rate of 2-10°C / min, keep warm for 10-60 min, then heat to 800-950°C at a heating rate of 2-10°C / min, keep warm for 20-60 min, so as to achieve effective connection between the base material to be welded and the composite sealing material, then cool to 400°C at a cooling rate of 2°C / min, and finally cool the seal with the furnace.

9. A composite sealing material for medium-temperature solid oxide fuel cells according to claim 8, characterized in that: In step (1), the electrolyte ceramic is one of YSZ ceramic, ScSZ ceramic or GDC ceramic; the connector stainless steel is one of Crofer22H, Crofer22APU, 430 stainless steel or 441 stainless steel.

10. The composite sealing material for medium-temperature solid oxide fuel cells according to claim 8, characterized in that: In step (1), the thickness of the composite sealing material coated on the surface of the base material to be welded is 50-300 μm.

Citation Information

Patent Citations

  • Microcrystal glass sealing material used for solid oxide fuel battery and sealing method thereof

    CN101148322B

  • A high-temperature composite sealing material and its application

    CN112928299B

  • Composite sealing material for solid oxide fuel cell as well as preparation method and application of composite sealing material

    CN114436533A

  • Method of Producing Metal to Glass, Metal to Metal or Metal to Ceramic Connections

    US20080142148A1